2020
DOI: 10.1111/ggi.13868
|View full text |Cite
|
Sign up to set email alerts
|

Low alanine aminotransferase levels predict low muscle strength in older patients with diabetes: A nationwide cross‐sectional study in Korea

Abstract: Aim Low alanine aminotransferase (ALT) level is associated with frailty in the older adult population. We investigated the usefulness of ALT in predicting low muscle strength among older patients with diabetes. Methods We included 550 men aged ≥50 years and 525 postmenopausal women. All participants had diabetes, and data were based on the 2014–2016 Korea National Health and Nutrition Examination Survey. Participants with ALT levels confounded by hepatic causes or who had a cerebrovascular accident were exclud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…ALT levels can be increased by release from adipocytes in obese patients. Conversely, the amount of ALT released from the skeletal muscle decreases in patients with sarcopenia 26 . In this study, these factors may not have made ALT as a risk factor for bile leakage in HCC patients.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…ALT levels can be increased by release from adipocytes in obese patients. Conversely, the amount of ALT released from the skeletal muscle decreases in patients with sarcopenia 26 . In this study, these factors may not have made ALT as a risk factor for bile leakage in HCC patients.…”
Section: Discussionmentioning
confidence: 67%
“…Conversely, the amount of ALT released from the skeletal muscle decreases in patients with sarcopenia. 26 In this study, these factors may not have made ALT as a risk factor for bile leakage in HCC patients. Liver resection with broad exposure of the hilar Glissonean sheath is considered as a high-risk procedure 27 that may lead to bile leakage.…”
Section: Discussionmentioning
confidence: 76%
“…(13,16) It was recently shown that low ALT levels are associated with reduced muscle strength, adverse outcomes in the general population of hospitalized patients, patients with chronic obstructive pulmonary disease exacerbation, and rehabilitation program participants. (12,15,16,32) To the best of our knowledge, this is the rst study to assess the correlation between low ALT and extubation failure.…”
Section: Discussionmentioning
confidence: 99%
“…Serum ALT is a readily available, inexpensive, and routine biochemical assay used in clinical practice. A large number of studies have established the association between low ALT levels and sarcopenia and frailty in both middle-aged [ 22 ] and elderly patients [ 16 , 37 ] and in a myriad of clinical contexts [ 18 , 19 ]. A prospective study of 179 patients in an internal ward found that low ALT blood activity and high Frail questionnaire score correlated with increased mortality and with each other [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, when the liver parenchyma is intact, ALT blood levels (demonstrated as catalytic activity) are a good marker for the whole-body skeletal muscle mass [ 14 , 15 ]. Utilizing the aforementioned, a large body of evidence accumulated in the past years, marking lower ALT values as a reliable marker for sarcopenia and frailty, in large, heterogeneous patient populations [ 16 , 17 , 18 , 19 ]. Characterizing sarcopenia and frailty status in patients with HF may provide clinicians with an indicator for gauging disease severity, prognosis, and disease progression or reversal.…”
Section: Introductionmentioning
confidence: 99%